Interrelated Effects of Temperature and Moisture on Seed Germination of Dendrocalamus strictus Nees - Gupta, B. N.; Kumar, Adarsh (Indian Forester, 1977)
Effect of five constant and three alternating temperatures viz, 20°C, 25°C, 30°C, 35°C, 40°C, 20-30°C, 25-35°C and 30-40°C in combination with five moisture levels of substratuin viz. 25%, 50%.75%,100% and 125% was studied on the germination of Dendrocalamu striclamus seedss. It was observed that 30°C is the ideal temperature for germination since this brought out the maximum and quickest seed germination. 40°C was found to be detrimental for germination. 20°C was also not found to be favourable as the rate of germination at this temperature was slow. Alternating temperatures also did not record any edge over constant temperatures. Moisture status of substratum was loaud to be a controlling factor. 125% moisture at all temperatures proved fatal and 25% moistare in moot of the cases was observed to be insufficient to briDg in the desired level of Hydration. 5O to 75% moiature level was recorded to be the optimum.